Catch-Up Growth Evaluation after Liver Transplant.Experience in Fundacion Valle del Lilí. (July 2018) - Botero, Veronica; Jaramillo, Carolina; Bustos, Jenny A; Manzi, Eliana; Caicedo, Luis A; Garcia, Victor H
Abstract : Introduction: Liver transplantation in children with acute or chronic liver failure is a curative option that has proven to improve the survival of this group of patients for almost two decades, yet, the knowledge gap remains in the quality of life of this patients, and the impact en nutritional status. In our country, there are note studies published that evaluate the catch-up growth in liver transplanted children. The aim of our study is to described the nutritional status of the patients in the prestansplant period, and described the changes in the growth chart in patients younger than 10 years old. Materials and Methods: Our study is a retrospective case series. The information was gathered from medical records registered in the liver transplant data base, from patients that were transplanted between January 2012 and December 2015. A total of 77 patients achieved all the inclusion criteria for the study. Results: During the period studied, a total of 54 patients had an alteration in the weight for age, at the end of the evaluated period 89% patients catch-up the ideal weigh for age. 56 patients were under the appropriate length for age, at the end 39% get to catch up an adequate length for age. 46 patients had an altered weigh for length or IMC for Length and a 56% of the patients got in adequate ranges. The patients younger than 2 years old had a catch up that was statistically significant. Conclusion: Liver transplant improves the anthropometric measures in patients with liver disease, and the majority of the receptors get a catch up according to age. Regarding to the length, the patients got an augmentation in the growth velocity, not reaching the adequate range for age, but going through low length for age to risk of low length for age. The liver transplant performed early in children younger than two years, impacts in an early and late state of chronic liver disease.